A designed plasmid‐transition strategy enables rapid construction of robust and versatile synthetic exoelectrogens for environmental applications. (6th September 2022) - Fan, Yang‐Yang; Tang, Qiang; Sun, Hong; Yu, Han‐Qing
Abstract: Genetic engineering is promising to expand the application scope of exoelectrogens in energy and environmental applications and plasmid vectors, as one type of fundamental tool, are intensively applied. Antibiotics are widely utilized for plasmid selection and maintenance; however, their utilization suffers from environmental concerns on the spread of resistance genes, elevated costs, inevitable genotypic instability and phenotypic heterogeneity. In this work, we establish an auxotrophic complementation system for stable plasmid maintenance without antibiotic association, in Shewanella oneidensis, an attractive model exoelectrogen. A plasmid‐transition strategy is designed to facilitate the rapid and efficient construction of the auxotrophic complementation system. Such a system not only enables the same intensive gene expression as the conventional antibiotic‐associated plasmid system but also exhibits remarkably superior robustness and stability. With this system, the menaquinone pool of the extracellular respiratory chain is enhanced first independently and further synergized by engineering the Mtr conduit, leading to significantly promoted extracellular electron transfer (EET) outputs (up to 10.33‐ and 2.97‐fold improvement in the maximum current density and the maximum output voltage) and heavy metal Cr(VI) reduction ability (5.15‐fold improvement). This work provides a robust and stable platform to engineer exoelectrogens for environmental applications.